Improvement in Survival Outcomes of Acute Lymphoblastic Leukemia Patients Treated With Berlin-Frankfurt-Munster 76/79 Protocol - Khansa Saleem; Muhammad Ilyas; Saad Razzaq; Fahad Maqbool; Qaiser Abbas; Aneem Abdullah; Abu Bakar Shahid (Proceedings, 2021)
Introduction: Acute lymphoblastic leukemia (ALL) is a malignancy of the white blood cells and lymphoid lines of hematopoietic cells in the blood and bone marrow while lymphomas mostly involve the lymph nodes. This study showed the response rate of ALL treated with BFM (Berlin-Frankfurt-Munster) 76/79 protocol.